2011
DOI: 10.3109/00365521.2011.551886
|View full text |Cite
|
Sign up to set email alerts
|

Through-the-scope large diameter self-expanding metal stent placement as a safe and effective technique for palliation of malignant colorectal obstruction: A single center experience with a long-term follow-up

Abstract: In our experience, TTS large-diameter SEMS placement is a safe and effective treatment for palliation of malignant colorectal obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Recently, various types of stents have been introduced to prevent complications after SEMS placement. Uncovered SEMSs with a larger diameter or finer mesh can maintain luminal patency, and covered SEMSs with uncovered ends, flared ends, or inner membranes can reduce the migration rate [25][26][27]. In our study, SEMS treatment had high technical and clinical success rates as a palliative treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, various types of stents have been introduced to prevent complications after SEMS placement. Uncovered SEMSs with a larger diameter or finer mesh can maintain luminal patency, and covered SEMSs with uncovered ends, flared ends, or inner membranes can reduce the migration rate [25][26][27]. In our study, SEMS treatment had high technical and clinical success rates as a palliative treatment.…”
Section: Discussionmentioning
confidence: 74%
“…In this setting, colonic stents represent the best option when skills are available [7] . [18] 2008 51 51 (100) 43 (84.3) 1 (1.9) Fernández-Esparrach et al [19] 2010 47 44 (94) 44 (94) 3 (7) Small et al [20] 2010 233 224 (96.1) 222 (95.2) 18 (7.7) Park et al [21] 2010 151 149 (98.6) 140 (92.7) 0 Branger et al [22] 2010 93 86 (92.5) 80 (86) 3 (3.2) Donnellan et al [23] 2010 43 40 (93) 40 (93) 2 (4.6) Lee JH et al [24] 2010 46 46 (100) 39 (84.8) 2 (4.3) Lee HJ et al [25] 2011 71 68 (95.8) 68 (94) 4 (5.6) Luigiano et al [26] 2011 39 36 (92.3) 35 (89.7) 2 (5.1) Jiménez-Pérez et al [27] 2011 182 177 (98) 141 (94) 5 (3) Tominaga et al [28] 2012 24 24 (100) 20 (83) 0 Yoshida et al [29] 2013 33 33 (100) 32 (97) 0 Bonfante et al [30] …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the above-mentioned study identified the length of stenosis as an independent predictor of complications. This has been previously debated in several studies with conflicting results: (1) 3 studies reported that stenting of a long obstructed segment was not associated with clinical failures [31][32][33] ; (2) however, in 2 retrospective studies, a better outcome was observed in short colon strictures [2,3] . One of these retrospective studies reported more technical failures in strictures >4 cm (OR 5.33) and even clinical failures (OR 2.40) [3] .…”
mentioning
confidence: 78%